Пути повышения биоконверсии технического глицерина в поверхностно-активные вещества Rhodococcus erythropolis IMВ Aс-5017, Aсinetobacter calcoaceticus IMВ B-7241 и Nocardia vaccinii IMВ B-7405 - Пирог, Татьяна Павловна; Шевчук, Татьяна Андреевна; Мащенко, Оксана Юрьевна (My University, 2015)
Исследовали возможность синтеза поверхностно-активных веществ (ПАВ) Rhodococcus erythropolis IMВ Ac-5017, Aсinetobacter calcoaceticus IMВ B-7241 и Nocardia vaccinii IMВ B-7405 в среде с высокой (до 8 % по объему) концентрацией технического глицерина – отхода производства биодизеля. The possibility of surface-active substances (SAS, biosurfactants) synthesis under cultivation of Rhodococcus erythropolis IMВ Ac-5017, Aсinetobacter calcoaceticus IMВ B-7241 and Nocardia vaccinii IMВ B-7405 in the medium with high (to 8 %, v/v) concentration of crude glycerol – by-product of biodiesel production was investigated.
Keywords: кафедра біотехнології і мікробіології; Rhodococcus erythropolis IMB Ac-5017; Aсinetobacter calcoaceticus IMВ B-7241; Nocardia vaccinii IMB В-7405; интенсификация биосинтеза; поверхностно-активные вещества; технический глицерин; intensification of biosynthesis; biosurfactants; crude glycerol